Pemberdayaan Kemampuan Lansia Dalam Deteksi Dini Penyakit Degeneratif - Widodo Widodo; Sumardino Sumardino (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: Awareness, Early Detection Capabilities, And Community Empowerment. This study aims to improve the ability of elderly people in the early detection of degenerative diseases in Posyandu Melati III Tegalrejo, Ceper, Klaten. While the specific purpose of this study was to describe the initial knowledge of early detection of degenerative diseases, describing the changes of knowledge and capacity for early detection of degenerative diseases post-counseling and training. This study used a quasi-experimental research design (queasy-experiment). The data source of this research is a group of elderly Posyandu Bed III Tegalrejo, Ceper, Klaten with the method of selecting a sample is total population. The tools used in this study was a questionnaire to evaluate the cognitive, psychomotor aspects SOP to evaluate and extension materials. Results showed that changes in knowledge and capacity for early detection of the elderly against degenerative diseases in Posyandu Melati III Tegalrejo, Ceper, Klaten. This is evident from the test results of paired t-test with a significance value of 0.000> 0.05. The provision of health education and training early detection of degenerative diseases can increase knowledge of the initial capital to raise public awareness about the importance of early detection capabilities against degenerative diseases so that the quality and degree of health of the elderly can be optimized.